College Tutors’ Barriers and Challenges with their usage of Online Instructional Delivery Resources during Covid-19 Pandemic, Ghana. - Obeng Owusu-Boateng; Issifu Yidana; Anas Seidu Salifu; Ben-Bright Benuwa; Gilbert Naa Emmideme; Khalid Abdul-Mumin; Ben Kudus Yussif (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
The study investigates the barriers and challenges Ghanaian College tutors faced during the Covid-19 Pandemic when schools had to be closed down which necessitated teaching and learning to be transitioned from the normal face-to-face to a completely online mode using online instructional delivery resources. The research design was descriptive statistics with a sample size of 100 tutors chosen from ten Colleges of Education in Northern Ghana. A purposive sampling technique was used to choose these tutors. The instrumentation used for data collection in this study was a questionnaire. A closed-ended questionnaire was developed for this study. An online Google Forms questionnaire was used to elicit responses using a 4-point Likert scale and the data was analyzed using IBM SPSS version 20. The results of this study found that, the major barriers identified by tutors in the usage of online instructional delivery resources during teaching and learning included; constant cuts in electricity supply, high cost of electronic devices, high cost of maintenance for electronic devices used for online teaching, poor internet connectivity, low level of incentives, low-level internet accessibility, high cost of data bundle and lack of incentives and motivation. The findings of this study....